miR-148b Regulates Proliferation and Differentiation of Neural Stem Cells via Wnt/β-Catenin Signaling in Rat Ischemic Stroke Model - Wang, Jingru; Chen, Tuanzhi; Shan, Guangzhen (Frontiers in Cellular Neuroscience, 2017)
Stroke is the second leading cause of death worldwide. Stroke induced proliferation and differentiation of neural stem cells (NSCs) that have been proven to participate in ischemic brain repair. However, molecular mechanisms that regulate neurogenesis have not been fully investigated. MicroRNAs play an important role in the neurological repairing process and impact stroke recovery outcome. MiRNA-148b has been reported to regulate cell proliferation in tumor cells, but its role in NSCs after ischemic stroke remains unknown. Here, we found an overexpression of miRNA-148b in subventricular zone (SVZ) of rat ischemic brain. In original cultured ischemic NSCs, transfection of miRNA-148b mimic or inhibitor could suppress or enhance the expression of Wnt-1, β-catenin and Cyclin D1, hence effected wnt/β-catenin signaling. MiRNA-148b inhibitor promoted NSCs proliferation and differentiation into newborn neural and astrocytes, and this action could be silenced with knockdown of Wnt-1. In middle cerebral artery occlusion (MCAo) rats, injection of miRNA-148b inhibitor could reduce ischemic lesion volume and improve neurological function outcome. Collectively, our data suggest that miRNA-148b suppressed wnt/β-catenin signaling attenuates proliferation and differentiation of neural stem cells, these findings shed new light on the role of miRNA-148b in the recovery process during the stroke and contribute to the novel therapy strategy.